2021
DOI: 10.1177/15910199211030780
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results and comparison of flow re-direction endoluminal device and pipeline embolization device in endovascular treatment of intracranial carotid aneurysms

Abstract: Objective This study aims to compare the efficacy, safety, and long-term outcomes of two flow diverters, i.e., pipeline embolization device and flow re-direction endoluminal device, in the treatment of distal carotid aneurysms. Methods A total of 138 patients with 175 aneurysms were included from February 2012 to September 2019. Ninety-nine aneurysms were treated with flow re-direction endoluminal device and 76 with pipeline embolization device. Angiographic follow-ups were at the 6th, 12th, 24th, 36th, and 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
(31 reference statements)
2
8
0
Order By: Relevance
“…All the complications in the FRED group were cases of mild in-stent stenosis, the rate of which was double than that experienced in the PED group (15.2% vs 6.9%; OR = 2.411). This corroborates the findings presented in the study by Gündogmus ¸et al 16 where all 5 case of instent stenosis were observed in the FRED-treated group compared with none in the PED group. In their study, 2 patients treated with FRED developed asymptomatic but severe in-stent stenosis after 1 year, 1 of which progressed to asymptomatic total occlusion by the second year.…”
Section: Complicationssupporting
confidence: 92%
See 1 more Smart Citation
“…All the complications in the FRED group were cases of mild in-stent stenosis, the rate of which was double than that experienced in the PED group (15.2% vs 6.9%; OR = 2.411). This corroborates the findings presented in the study by Gündogmus ¸et al 16 where all 5 case of instent stenosis were observed in the FRED-treated group compared with none in the PED group. In their study, 2 patients treated with FRED developed asymptomatic but severe in-stent stenosis after 1 year, 1 of which progressed to asymptomatic total occlusion by the second year.…”
Section: Complicationssupporting
confidence: 92%
“…To the best of our knowledge, there are only 3 studies in the literature comparing the only 2 FDA-approved flow-diverting stents, FRED and PED. 4,15,16 Our IPW-adjusted study represents the only study directly comparing both flow diverters in the treatment of anterior and posterior circulation aneurysms at a single institution in the United States. No statistically significant differences in complete occlusion rates at 6 months, functional outcome, length of stay, or complication rate were found between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Post-treatment complications, specifically in FRED-treated cohort, although reported as mild, are similar to what has been previously reported in the study by Gündogmus et al 3 where in-stent stenosis was observed only in the FRED-treated group compared with none in the PED group. Studies by Hagen et al 15 and Girdhar et al 16 examined the thrombogenicity of PED and FRED in ex-vivo and in vitro models with and without antiplatelet medication and dual antiplatelet therapy.…”
supporting
confidence: 89%
“…[5][6][7] By doing this, they make it possible to repair the parent artery's mural insufficiency, occluding the aneurysm permanently and resolving it over. [1][2][3][4][5]8,9 The 2 Food and Drug Administration-approved flow diverters, pipeline embolization device (PED) and flow redirection endoluminal device (FRED), have demonstrated excellent results in treating unruptured aneurysms in numerous studies conducted internationally, enabling minimally invasive therapy of intracranial aneurysms. [2][3][4][7][8][9][10][11][12][13] The potential for these devices to target and treat aneurysms of diverse sizes, shapes, and even different cerebral sites that have not yet been thoroughly submitted to prospective investigation is quite promising.…”
mentioning
confidence: 99%
See 1 more Smart Citation